EBV positive extranodal NK/T cell lymphoma presenting as intestinal lymphoma- A diagnostic challenge - Nitya Prabhakaran; Katsiaryna Laziuk; Richard D. Hammer (Elsevier, 2019)
The World Health Organization (WHO) recognizes aggressive natural killer (NK)-cell leukemia and extranodal NK/T-cell lymphoma, nasal type as Epstein Barr Virus (EBV) associated lymphoproliferative disorders that may have overlapping features and must be distinguished from other T-cell lymphomas. A 35-year-old Hispanic female presented with fever of unknown origin, hemolysis and pancytopenia. Bone marrow biopsy with flow cytometry was negative for malignancy. Jejunal resection was performed due to concern for perforation and demonstrated a high-grade lymphoid neoplasm. Immunohistochemical stains showed that the neoplastic cells are positive for CD3, CD30, CD56 and cytotoxic markers Granzyme and TIA-1. EBV encoded RNA (EBER) was strongly positive in neoplastic cells. The location and immunophenotype first raised consideration of intestinal T-cell lymphoma, not otherwise specified (NOS). However, EBER positivity is characteristic of extranodal NK/T-cell lymphoma, nasal-type involving the small bowel. The patient soon expired and autopsy demonstrated hepatosplenomegaly with scattered nodules of necrosis with neoplastic cells morphologically similar to those in the jejunum and involving the hepatic sinusoids and splenic red pulp. Overlapping morphology and immunophenotype, lack of specific cytogenetic and molecular abnormalities makes the diagnosis of EBV associated extranodal NK/T cell leukemia/lymphomas challenging. EBER studies are mandatory to differentiate from Intestinal T cell lymphoma NOS. Early diagnosis of this aggressive malignancy is crucial in expediting appropriate treatment. Keywords: Extranodal NK/T cell nasal type lymphoma, EBER, Intestinal lymphoma